Sex Differences in Social Adaptive Function in Autism Spectrum Disorder and Attention-Deficit Hyperactivity Disorder - Mahendiran, Tania; Dupuis, Annie; Crosbie, Jennifer; Georgiades, Stelios; Kelley, Elizabeth; Liu, Xudong; Nicolson, Robert; Schachar, Russell; Anagnostou, Evdokia; Brian, Jessica (Frontiers in Psychiatry, 2019)
Background: Social-communication difficulties, a hallmark of ASD, are often observed in ADHD, although not part of its diagnostic criteria. Despite sex differences in the prevalence of ASD and ADHD, research examining how sex differences manifest in social and communication function in these disorders remains limited and findings are mixed. This study investigated potential sex differences with age in social-communication function in these disorders. Method: 115 youth with ASD, 172 youth with ADHD and 63 typically developing controls (age range 7-13 years, 75% males) were recruited from the Province of Ontario Neurodevelopmental Disorder (POND) Network. Social-communication function was assessed using the Adaptive Behavior Assessment System-Second Edition (ABAS-II). The proportion of adaptive behaviors present in each skill area were analyzed as a binomial outcome using logistic regression, controlling for age and testing for an age by sex interaction. In an exploratory analysis, we examined the impact of controlling for core symptom severity on the sex effect. Results: Significant sex by age interactions were seen within ASD on the communication (p=0.005), leisure (p=0.003) and social skill areas (p<0.0001). In all three areas, lower scores (indicating poorer function) were found in females compared to males at older ages despite females performing better at younger ages. There were significant differences in the sex by age interactions in the social and leisure domains between those with ASD and typically developing controls, with typically developing females showing better scores with age. There were also significant differences in the sex by age interactions between ASD and ADHD on the social and leisure domains, as females with ADHD consistently scored higher on social skills than males across all ages, unlike those with ASD. Sex differences across age in the social domains for ADHD were similar to those in the typically developing group. Conclusion: Sex differences in social and communication skill areas were observed between ASD and ADHD, and typically developing controls, with females with ASD performing worse than males at older ages, despite an earlier advantage. These findings reinforce the need to take a developmental approach to understanding sex differences which may have diagnostic, prognostic and treatment implications.